Prenatal maternal life adversity impacts on learning and memory in offspring: implication to transgenerational epigenetic inheritance - Prince David Adeline Dorothy; Koilmani Emmanuvel Rajan (Frontiers in Neuroscience, 2025)
Maternal stress exposure during pregnancy is known to affect offspring behavior, including learning and memory. We hypothesized that maternal stress-induced changes transmit this effect through maternal line mediated transgenerational epigenetic inheritance. To test our hypothesis, pregnant rats (F0) were undisturbed (Control, Ctrl)/exposed to social stress during gestational days (GD) 16–18 (PMS)/exposed to social stress and treated with oxytocin during GD-16 to 18 (PMS+OXT). Subsequently, F1 female offspring from Ctrl, PMS, and PMS+OXT were mated with Ctrl F1 males to examine maternal line mediated transgenerational impacts. Female animals (F1 and F2) were subjected to behavioral test and the levels of global H3K4me2/H3K4me3 methylation, methylation in the CRH promoter, expression of Crh, Crh receptors (Crhr1, Crhr2), and BDNF were determined. It was found that prenatal maternal stress (PMS) reduced reference and working memory in F1 and F2 offspring, increased global and specific H3K4me2, H3K4me3 methylation in the CRH promoter, expression of Crh, Crh receptors, and corticosterone (CORT), and down-regulated the expression of pro-and mature BDNF by differentially regulating Bdnf transcripts III, IV and VI in the amygdala. Oxytocin exposure reduced PMS-induced global and specific H3K4me2/3 changes, which repressed the expression of Crh, Crh receptors, reduced CORT levels, up-regulated the expression of pro-BDNF and mature BDNF, and improved memory in F1 and F2 offspring. Collectively, our study revealed that PMS reduced reference and working memory performance in F1 and F2 offspring through maternal line transgenerational inheritance of H3K4me2, H3K4me3 methylation, and associated mechanisms that regulate BDNF expression and synaptic plasticity.